Pengembangan Modul IPA Berorientasi Profil Pelajar Pancasila Materi Ekologi dan Keanekaragaman Hayati Indonesia untuk Siswa SMP/MTs - Dewi, Ni Putu Diah Loriana; Juniartina, Putu Prima; Priyanka, Luh Mitha (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
The teaching materials in the form of modules used by students in learning are not yet fully linked to the Pancasila Student Profile as required by the Merdeka curriculum. The research aimed to develop a science module oriented to the Pancasila Student Profile for junior high schools that is valid, practical, and readable, focusing on ecology and Indonesian biodiversity. The development of the research model chosen, namely 4D (Define, Design, Develop, and Disseminate), because of time constraints, is limited to the development stage. Content, media, language, observations, and validity test subjects were each carried out by 2 expert validators from the Ganesha University of Education, and the practicality and readability test subjects involved 3 science teachers and 15 class VII students at SMPN 1 Sukasada. The research instruments are interview sheets, observations, and questionnaires. Characteristics of the science module, namely (1) The form of the science module is as a textbook in PDF and printed format. (2) Module activities use the Discovery Learning model. (3) The syntax of the Discovery Learning model in the module contains the Pancasila Student Profile dimensions. The results showed a validity test with calculations using the Gregory formula with a score of 1.00 in the very high validity category. Practicality and readability were assessed at 94% and 93%, respectively, demonstrating a high level of both attributes. Based on these results, it can be concluded that the Pancasila Student Profile-oriented science module that was developed meets the criteria of being very valid, very practical, and very readable, so it is worth continuing to the effectiveness testing stage.